Monsoon-driven Saharan dust variability over the past 240,000 years - Skonieczny, C. (Sci Adv, 2019)
Reconstructions of past Saharan dust deposition in marine sediments provide foundational records of North African climate over time scales of 10(3) to 10(6) years. Previous dust records show primarily glacial-interglacial variability in the Pleistocene, in contrast to other monsoon records showing strong precessional variability. Here, we present the first Saharan dust record spanning multiple glacial cycles obtained using (230)Th normalization, an improved method of calculating fluxes. Contrary to previous data, our record from the West African margin demonstrates high correlation with summer insolation and limited glacial-interglacial changes, indicating coherent variability in the African monsoon belt throughout the late Pleistocene. Our results demonstrate that low-latitude Saharan dust emissions do not vary synchronously with high- and mid-latitude dust emissions, and they call into question the use of existing Plio-Pleistocene dust records to investigate links between climate and hominid evolution.